Bilateral spatiotemporal postural control impairments are present in participants with chronic ankle instability. (September 2019) - Simpson, Jeffrey D.; Rendos, Nicole K.; Stewart, Ethan M.; Turner, Alana J.; Wilson, Samuel J.; Macias, David M.; Chander, Harish; Knight, Adam C.
Abstract: Objectives: This study evaluated center-of-pressure (COP) and time-to-boundary (TTB) measures of postural control during a Lateral Step-Down Test in participants with chronic ankle instability (CAI). Design: Cohort study. Setting: Biomechanics laboratory. Participants: Physically active adults with CAI (n = 15) and matched controls (n = 15). Main outcome measures: Traditional COP and TTB measures of postural control were computed in the medial/lateral (ML) and anterior/posterior (AP) directions. Results: No significant results were found for the traditional COP measures ( p  > 0.05). The CAI group exhibited a lower TTB ML absolute minimum on their affected limb compared to the matched limb of the control group ( p  < 0.001). Additionally, on average the CAI group displayed significantly lower TTB ML mean of minima ( p  = 0.004) and TTB standard deviation of minima in the ML ( p  < 0.001) and AP directions ( p  = 0.002) regardless of limb. Conclusions: Sensorimotor impairments associated with CAI negatively alter spatiotemporal postural control and may cause a maladaptive reorganization of centrally mediated motor control strategies that results in bilateral postural control deficits during the Lateral Step-Down Test. In addition, traditional COP measures did not reveal any postural control deficits suggesting that a spatiotemporal analysis should be used when assessing postural control in participants with CAI. Highlights: Deficits in postural control are associated with CAI. The Lateral Step-Down Test was completed on both limbs to assess postural control. Center of pressure measures did not reveal any significant differences in postural control. Spatiotemporal postural control deficts were found in individuals with CAI on both limbs.